From Sinicization to Modernization: The Evolution of Vietnamese Culture in the Shadow of China - Erari, Gregory Henry; Santoso, Made Panji Teguh (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to analyze the evolution of Vietnamese culture from the era of Sinicization to modernization, focusing on how Vietnam has maintained its cultural identity amid strong Chinese influence. The background of this study is Vietnam’s long history under Chinese domination for over a thousand years (111 BCE–939 CE), which brought significant changes to the Vietnamese language, governance, religion, and social structure. However, the process of Sinicization did not erase local identity; instead, Vietnam demonstrated strong adaptive and resistant cultural capabilities, which were further tested during French colonialism and the rise of modern globalization. The research employs an interdisciplinary approach, combining historical analysis, cultural studies, and cross-cultural comparison. Data were collected from primary sources such as Vietnamese historical manuscripts, Chinese dynastic records, French colonial documents, and secondary sources including international scholarly works. The analysis was conducted chronologically and thematically to identify patterns of cultural adaptation and resistance. Results show that while Vietnamese culture adopted many Chinese elementssuch as Han script, Confucianism, and architecture Vietnam succeeded in developing its own writing system (Chữ Nôm), syncretic religious forms, and a strong national identity. In the modern era, Vietnam continues to transform while retaining local cultural characteristics amid global influences. This study affirms that the strength of Vietnamese culture lies in its ability to selectively adapt without losing its core identity.